The Dynamic Response of Sea Ice to Warming in the Canadian Arctic Archipelago. Issue 22 (21st November 2019) - Howell, Stephen E. L.; Brady, Mike
Abstract: Ice arches in the Canadian Arctic Archipelago (CAA) block the inflow of Arctic Ocean ice for the majority of the year. A 22 year record (1997–2018) of Arctic Ocean‐CAA ice exchange was used to investigate the effect of warming on CAA sea ice dynamics. Larger ice area flux values were associated with longer flow duration and faster ice speed facilitated by increased open water leeway from the CAA's transition to a younger and thinner ice regime, which together have contributed to a significant ice area flux increase (10 3 km 2 /year) from Arctic Ocean into the northern CAA from 1997 to 2018. Remarkably, the 2016 Arctic Ocean ice area flux into the CAA (161 × 10 3 km 2 ) was 7 times greater than the 1997–2018 average (23 × 10 3 km 2 ) and almost double the 2007 ice area flux into Nares Strait (87 × 10 3 km 2 ). Continued warming may result in the CAA becoming a larger outlet for Arctic Ocean ice area loss. Plan Language Summary: Satellite observations are used to understand the effect of warmer temperatures on how much sea ice is transferred between the Canadian Arctic Archipelago (CAA) and the Arctic Ocean. Larger sea ice area flux values are associated with (i) longer flow duration, (ii) faster moving ice, and (iii) more open water leeway from the CAA's long‐term transition to a younger and thinner ice regime. These factors have contributed to a significant increase in the amount of sea ice entering the northern regions of the CAA from 1997 to 2018. Remarkably, the amount of Arctic Ocean ice entering the CAA in 2016 was 7 times larger the 1997–2018 average and almost double that of the amount of ice transported through Nares Strait in 2007. Overall, with continued warming the CAA could be larger pathway for the loss of sea ice in the Arctic Ocean. Key Points: Significant increase of Arctic Ocean ice area flux into the northern CAA from 1997 to 2018 Arctic Ocean ice area flux into the CAA in 2016 was 7 times greater than 1997–2018 average Continued warming may result in the CAA becoming a larger outlet for Arctic Ocean ice area loss